Risk factors and predictors of hypothermia and dropouts during open-water swimming competitions - Drigny, J.; Rolland, M.; Pla, R.; Chesneau, C.; Lebreton, T.; Marais, B.; Outin, P.; Moussay, S.; Racinais, S.; Mauvieux, B. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To measure core temperature (Tcore) in open-water (OW) swimmers during a 25-km competition and identify the predictors of Tcore drop and hypothermia-related dropouts.